(untitled) (Applied Biological Research, 2023)
Low-density lipoprotein receptor-related protein 5 (LRP5) is a protein, encoded by the LRP5 gene in humans. LRP5, the key component of the LRP5/LRP6/ Frizzled co-receptor group is involved in canonical Wnt pathway, a regulator of bone metabolism. Mutations in LRP5 can lead to considerable changes in bone mass following bone diseases. Our study aimed to predict the effect of missense SNPs in human LRP5 gene by in silico methods using publicly available online software tools and database. We predicted the functional effects of mutations by using VEP, PROVEAN, SNPs & GO, and PANTHER, effects on the stability of the protein by I-Mutant 2.0 and on the 3-Dstructure of the protein by Project HOPE. We used GeneMANIA to predict the interaction of LRP5 with 20 other genes. Over all this is a comprehensive study provides all the available information about the clinically significant missense SNPs of LRP5 at a glance.